Hambatan Dan Alternatif Solusi: Peningkatan Keaktifan Siswa Dalam Pembelajaran Ppkn Di Sekolah Menengah Atas - Rouli Br Lumban Batu; Viona Francesca Purba; Nadira Zawani; Devi Sri Wahyuni; Bayu Ardian Syahputra; Fazli Rachman (Interdisciplinary Explorations in Research Journal, 2023)
This research aims to explore the challenges and learning media of Pancasila and Civic Education (PPKn) in high schools through a qualitative approach. The focus of this case study is high school students, where in-depth interviews and participatory observations were employed to gather contextual data. Thematic analysis was conducted to identify patterns and main themes from the interviews and observations. The findings of the research reveal a profound understanding of high school students regarding the challenges in learning PPKn, involving their perceptions of the utilized learning media. Conclusions are drawn through synthesizing the findings, considering the differences and similarities in students' perspectives. The qualitative method was chosen for its efficiency in providing an in-depth understanding of students' perceptions within a limited timeframe. This research contributes to a better understanding of the dynamics of PPKn learning in high schools and lays the foundation for further improvements in the learning process. Penelitian ini bertujuan untuk mengeksplorasi tantangan dan media pembelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn) di SMA melalui pendekatan kualitatif. Fokus studi kasus ini adalah siswa SMA, di mana wawancara mendalam dan pengamatan partisipatif digunakan untuk mengumpulkan data kontekstual. Analisis data dilakukan dengan pendekatan tematik untuk mengidentifikasi pola dan tema utama dari wawancara dan observasi.Hasil penelitian mengungkapkan pemahaman mendalam siswa/I SMA terhadap tantangan dalam pembelajaran PPKn, serta melibatkan persepsi mereka terhadap media pembelajaran yang digunakan. Kesimpulan ditarik melalui sintesis temuan, mempertimbangkan perbedaan dan persamaan pandangan siswa. Metode kualitatif dipilih karena memberikan pemahaman mendalam terkait persepsi siswa dalam batas waktu yang efisien. Penelitian ini memberikan kontribusi pemahaman yang lebih baik terhadap dinamika pembelajaran PPKn di SMA dan memberikan landasan bagi perbaikan lebih lanjut dalam proses pembelajaran ini.